REKONSTRUKSI KURIKULUM UNTUK MENUMBUHKAN CINTA BELAJAR BAHASA ARAB PADA ANAK USIA DINI - Aziz, Muhammad Tareh; Rido’i, Muhammad (MAANA: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to analyze the paradigm and concept of the Arabic language curriculum for early childhood education in accordance with the principles of Developmentally Appropriate Practice (DAP). The research method used is library research by examining various relevant literature on curriculum design, teaching methods, and assessment in Arabic language learning for young children. The results show that Arabic learning for early childhood should focus on fostering interest and love for the Arabic language rather than mastering its formal linguistic structure. Effective learning processes are carried out through thematic, integrative, contextual, and play-based approaches such as storytelling, songs, games, and Total Physical Response (TPR). The discussion reveals that enjoyable and spiritually oriented approaches can foster children’s intrinsic motivation to learn Arabic joyfully and sincerely. This study concludes that the Arabic language curriculum for early childhood should be humanistic and theocentric, aiming not only to develop linguistic competence but also to instill love for Allah and His Messenger.